Comparative Study of The Effect of Water Sample Preservation Variations and Spectrophotometer Types on Chemical Oxygen Demand (COD) Testing Results - Melati Ireng Sari; Zeolita Prabu Putri; Debi Anggun Sari; Dwi Indah Lestari (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Water is a primary need for all living things, especially humans, to support survival and daily activities. However, not all water can be used directly by humans. Wastewater cannot be reused without treatment because it is produced from various industrial and domestic activities. Before treatment, water samples must be examined first in the laboratory to determine their quality. However, because the nature of wastewater is easily changed, special handling is needed to maintain its condition. The water samples used were industrial wastewater (AI) and domestic wastewater (AD) with variations of preservatives (P) and without preservatives (TP). Meanwhile, the spectrophotometers used were the DR 5000 and Pharo 300 types. The lowest COD levels were produced in wastewater samples without preservatives (TP), namely 234.4 mg O2/l AI and 8,441.5 mg O2/l AD. The lowest RPD percentage was 0.287% AD-P using a DR 5000 spectrophotometer.